2016
DOI: 10.1007/s40607-015-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

A review of Longman Dictionary of Contemporary English (6th edition)

Abstract: Longman Dictionary of Contemporary English (6th edition) for advanced learners (LDOCE6), published by Pearson Education 2014, is the latest edition of this reputable dictionary for foreign learners of English. To increase its competitiveness, LDOCE6 includes new features like the Longman Communication 9000 to provide users with assistance on vocabulary acquisition, and the Grammar Guide to give information on major grammar topics and grammar notes that illustrate common grammar mistakes made by learners. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…An analysis of recent research and publications indicate that the problem of online dictionaries in the context of the digital transformation of education is attracting the attention of a lot of researchers. Ranka Stanković, Cvetana Krstev, Biljana Lazić and Mihailo Škorić have considered transformation electronic dictionaries -from file system to based lexical database [22]; Rastislav Metruk researched the use of electronic dictionaries for pronunciation practice by university students [13]; Anna Dziemianko investigated on the usefulness of paper and electronic dictionaries [1]; Sameer Naser Olimat found out the positive and negative impact of technology and information revolution on compiling the dictionary [17]; Robert Lew researched and classified the online dictionaries of English [11]; Amy Chi gave a review of Longman Dictionary of Contemporary English (6th edition) and found out whether the dictionary satisfies the needs and expectations of the users [3]. Christian M. Meyer and Iryna Gurevych explored the possibilities of collaborative lexicography by using Wiktionary [14]; Dikshit Kumar, Agam Kumar, Man Singh, Archana Patel and Sarika Jain clarified the difference between all existing online dictionaries and thesauruses by using an effective parameter [9]; Rezaei Mojtaba and Davoudi Mohammad found out the influence of electronic dictionaries on vocabulary knowledge extension [20]; Dmytro Pryimak found out the main mistakes of online dictionaries in the context of incomplete information, providing incorrect translations, and using incorrect lexical and grammatical constructions [19]; Ilona Kostikova highlighted the theoretical underpinnings of the efficiency of using electronic dictionaries at English lessons [8].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of recent research and publications indicate that the problem of online dictionaries in the context of the digital transformation of education is attracting the attention of a lot of researchers. Ranka Stanković, Cvetana Krstev, Biljana Lazić and Mihailo Škorić have considered transformation electronic dictionaries -from file system to based lexical database [22]; Rastislav Metruk researched the use of electronic dictionaries for pronunciation practice by university students [13]; Anna Dziemianko investigated on the usefulness of paper and electronic dictionaries [1]; Sameer Naser Olimat found out the positive and negative impact of technology and information revolution on compiling the dictionary [17]; Robert Lew researched and classified the online dictionaries of English [11]; Amy Chi gave a review of Longman Dictionary of Contemporary English (6th edition) and found out whether the dictionary satisfies the needs and expectations of the users [3]. Christian M. Meyer and Iryna Gurevych explored the possibilities of collaborative lexicography by using Wiktionary [14]; Dikshit Kumar, Agam Kumar, Man Singh, Archana Patel and Sarika Jain clarified the difference between all existing online dictionaries and thesauruses by using an effective parameter [9]; Rezaei Mojtaba and Davoudi Mohammad found out the influence of electronic dictionaries on vocabulary knowledge extension [20]; Dmytro Pryimak found out the main mistakes of online dictionaries in the context of incomplete information, providing incorrect translations, and using incorrect lexical and grammatical constructions [19]; Ilona Kostikova highlighted the theoretical underpinnings of the efficiency of using electronic dictionaries at English lessons [8].…”
Section: Related Workmentioning
confidence: 99%
“…For example, the Longman Dictionary marks all the words by special symbols: W1, W2, and W3 for words that are in the top 1000, 2000, and 3000 most frequent words in written English, and S1, S2, and S3 for the top 1000, 2000 and 3000 most frequent words in spoken English. Nowadays, many learner's dictionaries include information about the most frequent words in English, but Longman dictionaries are the only ones to highlight the differences between spoken and written frequency [3].…”
Section: Analysis Of Functionalities Online Platforms Of Dictionariesmentioning
confidence: 99%